2022
DOI: 10.1371/journal.pone.0267001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 distributes socially in China: A Bayesian spatial analysis

Abstract: Purpose The ongoing coronavirus disease 2019 (COVID-19) epidemic increasingly threatens the public health security worldwide. We aimed to identify high-risk areas of COVID-19 and understand how socioeconomic factors are associated with the spatial distribution of COVID-19 in China, which may help other countries control the epidemic. Methods We analyzed the data of COVID-19 cases from 30 provinces in mainland China (outside of Hubei) from 16 January 2020 to 31 March 2020, considering the data of demographic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Statistics published by the World Health Organization (WHO) show that more than four million premature human deaths are caused annually by the inhalation of fine particles [1] , [2] , [3] , [4] . In addition, more than six million people have died owing to the ongoing coronavirus (COVID-19) pandemic [5] , [6] , [7] , [8] . Personal protective masks offer the most direct and effective protection in daily life [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Statistics published by the World Health Organization (WHO) show that more than four million premature human deaths are caused annually by the inhalation of fine particles [1] , [2] , [3] , [4] . In addition, more than six million people have died owing to the ongoing coronavirus (COVID-19) pandemic [5] , [6] , [7] , [8] . Personal protective masks offer the most direct and effective protection in daily life [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Peng et al employed global autocorrelation analysis to elucidate the spatial pattern of COVID-19. Furthermore, they investigated the association between COVID-19 and diverse factors [2] . Ever since the onset of the COVID-19 pandemic, multiple studies have shown that various influencing factors have different effects on the spread and spatiotemporal distribution of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have modelled Covid-19 using a Bayesian spatial Conditional Autoregressive (CAR) considering socioeconomic influences. The association of socioeconomic, and environmental variables with the incidence of Covid-19 in the 30 provinces in mainland China has been identified using a Bayesian spatial CAR Besag, York & Mollié (BYM) model (Peng et al, 2022). Their results suggested that the risk of Covid-19 was positively correlated with the economic development level and population movements.…”
Section: Introductionmentioning
confidence: 99%